2022
DOI: 10.1002/pc.26524
|View full text |Cite
|
Sign up to set email alerts
|

Effects of aramid nanofibers on the mechanical properties of epoxy resin and improved adhesion with aramid fiber

Abstract: Inspired by the application of nano‐fillers in composite materials, well‐dispersed aramid nanofibers (ANFs) were prepared and added into the epoxy resin (EP) to improve the toughness and tenacity properties of the ANF/EP composites. The composites were characterized by mechanical property test, surface analysis, thermodynamic property analysis, and contact angle. Results showed that when the EP was added with 0.15 wt% ANF, the tensile strength, bending strength, and impact strength are increased by 28.2%, 81.9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 58 publications
(73 reference statements)
0
11
0
Order By: Relevance
“…Furthermore, currently, more efficient filler and reinforcement materials are available for applications to enhance overall mechanical properties, and these have been incorporated into epoxy systems. Some of the prominent examples can be listed as some metal oxides and sulfides such as micro and nano Ta 2 O 5 , 18 TiO 2 , and ZnS, 19 nano Al 2 O 3 , 20 graphene, 21 graphene oxide, 22 carbon nanotubes, 23,24 mineral fillers such as shungite 25 and wollastonite (CaSiO 3 ), 26 hollow glass microspheres, 27 micro and nano short fibers such as aramid, 28 and ultra‐high molecular weight polyethylene (UHMWPE) 29 . Moreover, hybrid systems of these filling and reinforcement materials such as graphene/carbon nanotube nanoplatelets, 23 graphene/alumina particles, 22 TiO 2 ‐filled poly(acrylonitrile‐butadiene‐styrene) ABS, 30 expandable graphite/ammonium phosphate, 31 multiple fillers such as TiO 2 /short CF/graphite/ZnS particles 19 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, currently, more efficient filler and reinforcement materials are available for applications to enhance overall mechanical properties, and these have been incorporated into epoxy systems. Some of the prominent examples can be listed as some metal oxides and sulfides such as micro and nano Ta 2 O 5 , 18 TiO 2 , and ZnS, 19 nano Al 2 O 3 , 20 graphene, 21 graphene oxide, 22 carbon nanotubes, 23,24 mineral fillers such as shungite 25 and wollastonite (CaSiO 3 ), 26 hollow glass microspheres, 27 micro and nano short fibers such as aramid, 28 and ultra‐high molecular weight polyethylene (UHMWPE) 29 . Moreover, hybrid systems of these filling and reinforcement materials such as graphene/carbon nanotube nanoplatelets, 23 graphene/alumina particles, 22 TiO 2 ‐filled poly(acrylonitrile‐butadiene‐styrene) ABS, 30 expandable graphite/ammonium phosphate, 31 multiple fillers such as TiO 2 /short CF/graphite/ZnS particles 19 .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, hybrid systems of these filling and reinforcement materials such as graphene/carbon nanotube nanoplatelets, 23 graphene/alumina particles, 22 TiO 2 ‐filled poly(acrylonitrile‐butadiene‐styrene) ABS, 30 expandable graphite/ammonium phosphate, 31 multiple fillers such as TiO 2 /short CF/graphite/ZnS particles 19 . Moreover, various surface treatment and functionalizing processes of these filling and reinforcement materials such as chemically treated UHMWPE and aramid fibers, 28,29 silane‐treated graphite nanoplatalets, 32 cation–π interaction‐assisted facile preparation of graphene, 21 and the grafting of any polymer with functional groups onto graphene oxide 33 have been more efficient in terms of enhancing the desired properties. However, these systems are not practical to implement, and they require complex processes despite to fact that significant improvements have been achieved with these filling and reinforcement materials in epoxy composites 17,34,35 .…”
Section: Introductionmentioning
confidence: 99%
“…Aramid fiber (AF) is a kind of special fiber with high strength, high modulus, excellent flame retardant, corrosion resistance and other excellent properties, and its development has received great attention in the material industry 30–36 . Due to the possibility of hydrogen bonding between AF and polymer, it can induce polymer crystallization 37 .…”
Section: Introductionmentioning
confidence: 99%
“…28,29 Aramid fiber (AF) is a kind of special fiber with high strength, high modulus, excellent flame retardant, corrosion resistance and other excellent properties, and its development has received great attention in the material industry. [30][31][32][33][34][35][36] Due to the possibility of hydrogen bonding between AF and polymer, it can induce polymer crystallization. 37 This microscopic molecular chain structure of AF determines the high temperature resistance of the fireproof grade, the mechanical performance of the bulletproof grade, the insulation performance of the high-pressure resistance grade and the corrosion of strong acid and alkali resistance grade.…”
mentioning
confidence: 99%
“…ANF maintains the similar crystal structure and mechanical properties to aramid fibers, while the surface is rich in polar functional groups such as carboxylic acids and amines. [39][40][41] ANF is a promising nano-sized building component in polymer reinforcement, [42,43] electrical insulation, [44][45][46] adsorption and filtration, [47][48][49] and supercapacitor electrodes. [50][51][52] It has been found that coating ANF on the surface of the fiber can improve the interfacial bonding between the fiber and the resin, [53] and ANF shows strong compatibility with the resin, which improves the strength, stiffness and toughness of the composite material.…”
mentioning
confidence: 99%